Reproductive health perspectives of young women with perinatally and behaviourally acquired HIV: A qualitative study. Issue 1 (7th July 2022) - Comfort, Lizelle; Watnick, Dana; Peskin, Melissa; Gutierrez, Julie; Abadi, Jacob; Atrio, Jessica
Abstract: Introduction: The aim of this study was to describe the sexual and reproductive goals of female adolescents with human immunodeficiency virus (HIV) in an urban cohort and decipher if they vary depending on the mode of HIV acquisition. Methods: We conducted in‐depth qualitative interviews with 25 Black and/or Hispanic/Latinx female adolescents living with HIV (14 perinatally, 11 behaviourally acquired) aged 17–25 years who have access to care and antiretroviral therapy at an urban public hospitals (NYC, NY). Interviews were transcribed, coded and analysed using thematic analysis. Results: Interviews demonstrated that access to antiretroviral therapy and HIV disclosure to a sexual partner were critical aspects of sexual health for the majority of participants. Persons with perinatal HIV defined motherhood as a source of self‐validation and were confident that antiretroviral therapy prevents HIV transmission. Persons with behaviourally acquired HIV viewed their status as an insurmountable barrier that will prevent them from attaining sexual intimacy with a partner and expressed persistent concerns about HIV transmission during pregnancy despite reassurance from medical providers. Conclusion: Sexual and reproductive perspectives of adolescents/young women living with HIV are multifactorial, highly stigmatized, and likely influenced by the mode of HIV acquisition. This population may benefit from patient‐centred care models, including sexual health counselling that addresses sexual agency, intimacy, parenting and transmission risk reduction. Practitioner points: Providers must acknowledge that young women living with human immunodeficiency virus (HIV) have basic sexuality concerns as well as pregnancy aspirations. Providers should recognize and communicate that, with the right immunovirologic parameters, women living with HIV can become pregnant with a very low risk of transmission to a serodiscordant partner and/or infant. HIV providers, particularly those caring for patients with behaviourally acquired HIV, should address the stigma that their patients may experience, and provide education and support when addressing disclosure, sexual activities and family planning goals. Consider referral  to perinatal HIV centres, which may be more focused on a holistic approach to HIV care for young women.